Strategi Komunikasi Visual Bujang Rimba dalam Membangun Brand Identity - Gilar Virgyawan; Riza Hernawati (UNISBA Press, 2024)
Abstract. Bujang Rimba is an advertising agency with a unique brand identity. This brand identity is shaped through the crucial role of visual communication. Visual communication involves the activity of visualizing creative ideas into cohesive visual products. Therefore, a creative process is necessary to produce unique visual products. This creative process is applied in every visual communication strategy, which includes managing visual elements, captions, and humor. All of these aspects are managed within a vernacular, vintage, and adaptive identity through a humorous approach. This research adopts a qualitative approach with descriptive case study analysis. The informants in this study are the Multimedia Director and Creative Designer of Bujang Rimba. Data collection techniques used include interviews, observations, and literature studies. Data analysis techniques used include data reduction, data presentation, drawing conclusions, and data validity. Based on the research findings, Bujang Rimba's creative process is divided into natural content and content based on brief. The management of Bujang Rimba's visual elements includes the profile picture and content of the @bujangrimba_ Instagram account. These visual elements include color, space, typography, illustration, shape, texture, and symbols. Caption management includes techniques of composition and message delivery. Meanwhile, humor is used to build a good relationship with the audience. Bujang Rimba aims for its audience to have an impressive, surprising, and enjoyable scrolling experience. Abstrak. Bujang Rimba merupakan agensi periklanan dengan brand identity yang unik. Brand identity dibentuk melalui peran penting komunikasi visual. Komunikasi visual melibatkan aktivitas memvisualisasikan ide kreatif menjadi produk visual yang utuh. Maka dari itu, diperlukan proses kreatif untuk menghasilkan produk visual yang unik. Proses kreatif tersebut diaplikasikan dalam setiap strategi komunikasi visual yang terdiri dari pengelolaan elemen visual, caption, dan humor. Seluruh aspek tersebut dikelola dalam identitas vernakular, jadul, dan adaptif melalui pendekatan humor. Penelitian ini menggunakan pendekatan kualitatif dengan analisis studi kasus deskriptif. Informan dalam penelitian ini adalah Multimedia Director dan Creative Designer Bujang Rimba. Teknik pengumpulan data yang digunakan adalah wawancara, observasi, dan studi kepustakaan. Teknik analisis data yang digunakan adalah reduksi data, penyajian data, kesimpulan, serta keabsahan data. Berdasarkan hasil penelitian, proses kreatif Bujang Rimba terbagi menjadi konten natural dan konten based on brief. Pengelolaan elemen visual Bujang Rimba meliputi profile picture dan konten akun Instagram @bujangrimba_. Elemen visual tersebut meliputi, warna, ruang, tipografi, ilustrasi, bentuk, tekstur, dan simbol. Pengelolaan caption, meliputi teknik penyusunan dan penyampaian pesan. Sedangkan pendekatan humor digunakan untuk menjalin hubungan yang baik dengan audiens. Bujang Rimba ingin audiensnya memiliki pengalaman scrolling yang berkesan, penuh kejutan, dan menyenangkan.